2011
DOI: 10.4049/jimmunol.1004218
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Dependent Phosphatidylinositol 3-Kinase/Akt and ERK Signaling Pathways Inhibit TLR3-Mediated Human Bronchial Epithelial Cell Apoptosis

Abstract: TLR3, one of the TLRs involved in the recognition of infectious pathogens for innate and adaptive immunity, primarily recognizes viral-associated dsRNA. Recognition of dsRNA byproducts released from apoptotic and necrotic cells is a recently proposed mechanism for the amplification of toxicity, suggesting a pivotal participation of TLR3 in viral infection, as well as in lung diseases where apoptosis plays a critical role, such as asthma and chronic obstructive pulmonary disease. In addition to metabolic contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…We also did not find any increase in the expression of the well-described FOXO target gene Bim, a proapoptotic factor of the Bcl-2 family that is induced upon several stress stimuli (24). Numata et al (36) reported that treatment of insulin-depleted HBEC with 10 mg/ml Poly-(I:C) leads to apoptosis via TLR3. The authors did not investigate the role of FOXO in these findings, but, considering our data, FOXO is a potential coeffector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also did not find any increase in the expression of the well-described FOXO target gene Bim, a proapoptotic factor of the Bcl-2 family that is induced upon several stress stimuli (24). Numata et al (36) reported that treatment of insulin-depleted HBEC with 10 mg/ml Poly-(I:C) leads to apoptosis via TLR3. The authors did not investigate the role of FOXO in these findings, but, considering our data, FOXO is a potential coeffector.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no difference in TLR3 transcription between knockdown and control cells. In a former study, it has been shown that Poly-(I:C) at 10 mg/ml induces TLR3-dependent cell death in respiratory epithelial cells (36). Therefore we assessed if cell death occurs in our particular setting.…”
Section: Foxo Mediates Tlr-3 Signalingmentioning
confidence: 99%
“…Cell cycle analysis and flow cytometry were performed as previously described [18]. Briefly, treated cells were harvested and immediately immobilized by 70% ice-cold ethanol overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining was performed as previously described (21). The primary Abs were applied according to the manufacturer's instructions.…”
Section: Preparation Of Csementioning
confidence: 99%